Differential activation of microglia in neurogenic versus non-neurogenic regions of the forebrain. - Goings, G; Kozlowski, D; Szele, F (2006)
Proliferation decreases in the neurogenic subventricular zone (SVZ) of mice after aspiration lesions of the cerebral cortex. We hypothesized that microglial activation may contribute to this given microglial activation attenuates neurogenesis in the hippocampus. Using CD45, CD11b, IB4, and IL-6 immunohistochemistry (IHC), BrdU IHC, and fluorescent bead tracking of peripheral monocytes into the brain, we compared microglial activation in the SVZ to non-neurogenic forebrain regions. SVZ microglia exhibited greater constitutive activation and proliferation than did microglia in non-neurogenic regions. In contrast to the SVZ, the dentate gyrus (DG) contained relatively few CD45(+) cells. After aspiration cerebral cortex lesions, microglia became activated in the cerebral cortex, corpus callosum, and striatum. SVZ microglial activation did not increase, and similarly, microglia in the DG were less activated after injury than in adjacent non-neurogenic regions. We next showed that SVZ microglia are not categorically refractory to activation, since deep cortical contusion injuries increased SVZ microglial activation. Macrophages migrate into the brain during development, but it is unclear if this is recapitulated after injury. Infiltration of microbead-labeled macrophages into the brain did not change after injury, but resident SVZ microglia were induced to migrate toward the injury. Our data show that both constitutive and postlesion levels of microglial activation differ between neurogenic and non-neurogenic regions.